The legend of Zorro - Campbell, Martin; Parkes, Walter F.; MacDonald, Laurie; Phillips, Lloyd; Columbia Pictures; Spyglass Entertainment (Firm); Amblin Entertainment (Firm) (Culver City, CA : Sony Pictures Home Entertainment, 2006)
This time, the legendary Zorro fights against evil-doers with the help of his beautiful wife, Elena, and their precocious young son, Joaquin. Alejandro De LaVega is torn between two worlds: his life as Zorro and his life as a family man. After Alejandro once again breaks his promise to stop wearing the mask, Elena leaves him, and she soon begins seeing Armand, a haughty French Count. But a mysterious explosion in the desert leads Zorro to believe that there's more to Armand than meets the eye. Zorro becomes intent on finding out what that is. Little does he know, there are others working to uncover certain truths as well
Originally released as a motion picture in 2005. Sequel to the 1998 motion picture The mask of Zorro
Features: optional commentary, deleted scenes, featurettes, multi-angle scene deconstructions
Title from title screen
Screenplay by Roberto Orci & Alex Kurtzman ; story by Roberto Orci ... [et al.] ; director of photography, Phil Meheux ; editor, Stuart Baird ; music, James Horner ; costume designer, Graciela Mazón ; production designer, Cecilia Montiel ; visual effects supervisor, Kent Houston
Cast: Antonio Banderas, Catherine Zeta-Jones, Rufus Sewell, Gustavo Sanchez Parra, Pedro Armendariz, Alberto Reyes, Julio Oscar Mechoso, Nick Chinlund
DVD Format
Keywords: Zorro (Fictitious character) -- Drama; Undercover operations -- Drama